(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Modern pharmaceutical science is predominantly grounded in a reductionist paradigm in which therapeutic efficacy is explained by the interaction of chemical matter with biological targets, governed by binding free energy and conformational dynamics at the molecular level. While this approach has achieved remarkable success in drug discovery and precision medicine, it often provides an incomplete account of clinical outcomes in complex, chronic, and psychosomatic conditions where context, expectation, and systemic regulation play decisive roles. In contrast, the Indonesian Jamu tradition conceptualized here through the framework of Jamulogi and the ancestral philosophy of Djampi Oesodo approaches healing as an integrated process involving kesadaran (consciousness), energi (biophysical and embodied regulation), and materi (biochemical substances derived from plants, animals, and minerals). This narrative integrative review compares modern pharmacy and Jamu as two distinct yet potentially complementary therapeutic paradigms. The analysis synthesizes evidence from molecular pharmacology, structural biology, placebo–nocebo neuroscience, systems and network pharmacology, ethnomedicine, archaeology, and environmental health. Modern pharmaceutical efficacy is examined through the lens of binding free energy (ΔG_bind) and protein–ligand conformational landscapes, while Jamu is analysed as a multi-component, multi-target system whose effects are modulated by consciousness-mediated expectation, ritualized therapeutic context, embodied techniques, and ecological continuity. Neuroscientific evidence demonstrates that expectation and belief can modulate endogenous opioidergic, neuroendocrine, autonomic, and immune pathways, providing biological validation for the therapeutic role of consciousness emphasized in Djampi Oesodo. Concurrently, systems pharmacology and natural product research support the plausibility of Jamu’s material domain as a network-level pharmacological intervention. The review argues that the apparent dichotomy between pharmacy and Jamu reflects differences in explanatory level rather than scientific incompatibility. By framing molecular binding energetics and systemic state regulation as complementary layers of therapeutic causality, Jamulogi emerges as a culturally grounded and scientifically plausible integrative health science. This framework offers a coherent foundation for future research in ethnopharmacology, systems biology, integrative clinical trial design, and sustainable phytopharmaceutical innovation within Indonesia and beyond.